2018
DOI: 10.1186/s12889-018-6200-4
|View full text |Cite
|
Sign up to set email alerts
|

Bathing adaptations in the homes of older adults (BATH-OUT): results of a feasibility randomised controlled trial (RCT)

Abstract: BackgroundHousing adaptations have been identified as an important environmental and prevention intervention for older adults, which may improve health and quality of life. The onset of disability in bathing can act as a warning for further disability in other activities and may therefore be a judicious time-point for intervention. The aim of this study was to determine the feasibility of conducting a Randomised Controlled Trial (RCT) of bathing adaptations, to evaluate whether they improve older adults’ perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…This study has highlighted a number of ways that bathing impacts, specifically both within the bathroom and more broadly, identifying a range of outcomes which are important to older adults and their carers. The findings were also consistent with the trends in improvement in the outcome measures used in the BATH‐OUT feasibility RCT (Whitehead et al, ), namely health and social care‐related quality of life, independence in daily living and reduced fear of falling. This has enabled us to draw comparisons, highlight measures for use in further practice and research, and to underpin the use of these measures with details of how these issues impact on lived experiences.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This study has highlighted a number of ways that bathing impacts, specifically both within the bathroom and more broadly, identifying a range of outcomes which are important to older adults and their carers. The findings were also consistent with the trends in improvement in the outcome measures used in the BATH‐OUT feasibility RCT (Whitehead et al, ), namely health and social care‐related quality of life, independence in daily living and reduced fear of falling. This has enabled us to draw comparisons, highlight measures for use in further practice and research, and to underpin the use of these measures with details of how these issues impact on lived experiences.…”
Section: Discussionsupporting
confidence: 84%
“…This study has highlighted a number of ways that bathing impacts, specifically both within the bathroom and more broadly, identifying a range of outcomes which are important to older adults and their carers. The findings were also consistent with the trends in improvement in the outcome measures used in the BATH-OUT feasibility RCT (Whitehead et al, 2018), namely health and social care- Overall, the difficulties were reported to stem from the physical barriers in the bathroom, the removal of which led to increased ease of use, a sense of 'freedom', and the older adults feeling better able to physically function in their environment. This finding could be framed within environmental press theory (Lawton & Nahemow, 1973) which postulates that an individual's competence in functioning is at its best when the environment is moderately challenging.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Provision of bathing adaptions therefore may delay functional deterioration, improve health and quality of life, and postpone the need for other health and social care services. 3 We previously completed a feasibility RCT of major bathing adaptations (BATH-OUT) 10 and a concurrent qualitative interview study. 11 Sixty adults aged 65 and over, and their carers, were randomised to expedited provision of bathing adaptations versus routine waiting list control.…”
Section: Open Accessmentioning
confidence: 99%